Visible-light-mediated C2-amination of thiophenes by using DDQ as an organophotocatalyst. Issue 26 (15th March 2017) - Song, Chunlan; Yi, Hong; Dou, Bowen; Li, Yiying; Singh, Atul K.; Lei, Aiwen
Abstract : A direct C–H amination of thiophenes was presented via an oxidation pathway under visible-light irradiation, in which the thiophene radical cation serves as the key intermediate. Various thiophenes and azoles could be transformed into the corresponding amination products well, and H2 O was the only byproduct, which is environmentally benign. Abstract : In this work, a direct C–H activation of thiophenes was presented via an oxidation pathway under visible-light irradiation, in which the thiophene radical cation serves as the key intermediate. Various thiophenes and azoles could be transformed into the corresponding amination products well, and H2 O was the only byproduct which is environmentally benign. Our results showed that tert -butyl nitrite (TBN) served as the electron transfer mediator and O2 as the terminal oxidant to regenerate the photocatalyst DDQ and revive the photocatalytic cycle.